Perancangan Aplikasi Absensi Karyawan Berbasis Web Menggunakan Metode Spiral Pada Wahyoo Group - Ahmad Ropii A.; Aditya Imam R.; Dede Hilmansyah; Nurul Muhtar; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
New technologies allow data transmission to move in seconds without geographical restrictions. With the emergence of global digital companies such as Google and Facebook, startups were born in Indonesia. The goal is to develop an attendance system that will facilitate data processing easily and quickly and help track employee check-ins and check-outs. To design this application, the spiral model was used, which is a combination of the prototype model and the waterfall model with a strong emphasis on risk analysis at each stage. The risk spiral model consists of five stages, namely linking, planning, analysis, engineering, and evaluation. The results of this study indicate that employees can speed up their work.